Outcome and treatment-related adverse events of combined immune checkpoint inhibition with flipped dosing in a real-world cohort of 79 patients with metastasized melanoma - Nübel, Charlotte; Amaral, Teresa; Leiter, Ulrike; Flatz, Lukas; Forschner, Andrea (Frontiers in Oncology, 2023)
Introduction Combined immune checkpoint inhibition (ICI) with ipilimumab and nivolumab is a widely used treatment regimen for metastatic melanoma with non-resectable metastases. Nevertheless, the standard dose of ipilimumab 3 mg/kg bw and nivolumab 1 mg/kg bw is associated with a high rate of treatment-related adverse events (trAEs) (59% grade 3–4). In the CheckMate 511 study, it could be shown that flipped dosing with ipilimumab 1 mg/kg bw and nivolumab 3 mg/kg bw resulted in a significant reduction of trAE. Methods We have also used this regimen in the clinical setting and report the trAE, progression-free survival, and overall survival for 79 patients with metastatic melanoma who started combined ICI in the flipped dosing between March 2019 and April 2020. Results in total, 40 patients started first-line, 50% of whom had an elevated lactate dehydrogenase level at baseline. The disease control rate of these patients was 50%. The 2-year overall survival rate 67%. Moreover, 33% of the patients suffered grade 3 or 4 treatment related adverse events. Discussion The results of our study correspond very well to the results of the CheckMate 511 study (2-year OS: 65%, grade 3-4 immune-related side effects: 35%). Combined ICI with ipilimumab 1 mg/kg bw and nivolumab 3 mg/kg bw seems to be an equally effective but better-tolerated therapy regimen for metastasized melanoma patients, also in a real-world cohort.